Edukasi Pijat Laktasi pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Jekan Raya Kota Palangka Raya - Cia Aprilianti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The failure to implement Exclusive Breast Milk (ASI) is often obtained in the early period after delivery because the milk has not yet been released is a reason for mothers to provide formula milk. This activity aims to provide lactation massage education for third-trimester pregnant women to increase breastfeeding. The activity was carried out in four meetings. The implementation of the activity went well, and the majority of participant characteristics were ideal (80%), multi-parity (70%), mothers with low education levels (70%), and mothers working as IRT (90%). It is hoped that outreach activities on lactation massage for pregnant women can be used as a routine program for health centers and health workers so that they can assist and prepare pregnant women with knowledge about exclusive breastfeeding before delivery.